Vitamins and Helicobacter pylori: An Updated Comprehensive Meta-Analysis and Systematic Review - Cai, Xianlei; Li, Xueying; Jin, Yangli; Zhang, Miaozun; Xu, Yuan; Liang, Chao; Weng, Yihui; Yu, Weiming; Li, Xiuyang (Frontiers in Nutrition, 2022)
Background: Over recent decades, epidemiological studies have shown relationships between vitamins and Helicobacter pylori (H. pylori) infection and eradication, but the results are controversial. Methods: A comprehensive meta-analysis and systematic review were conducted to clarify the relationships between common types of vitamins and H. pylori. We applied meta-regression, subgroup analysis and sensitivity analysis to obtain available evidence. Articles published from January 1991 to June 2021 in PubMed, EMBASE, and the Cochrane Library were searched. Results: In total, we identified 48 studies. The results indicate that H. pylori -positive patients had lower serum vitamin B12 [standardized mean difference (SMD) = - 0.30; 95% confidence interval (CI): - 0.53 - - 0.08], folate (SMD = - 0.69; 95% CI: -1.34 - - 0.04), vitamin C (SMD = - 0.37; 95%CI: - 0.57 - - 0.18) and vitamin D (SMD = - 0.34; 95% CI: - 0.49 - - 0.18) levels than H. pylori -negative patients. Patients in which H. pylori had been successfully eradicated had higher serum vitamin D levels (SMD = 1.37; 95% CI: 0.37 - 2.38) than in patients in which eradication had been unsuccessful. The serum vitamin B12 levels of H. pylori-positive patients improved after successful H. pylori eradication therapy (SMD = 1.85; 95% CI: 0.81 - 2.90), and antioxidant vitamin supplementation to an H. pylori eradication regimen improved the eradication rate (risk ratio = 1.22; 95% CI: 1.02 - 1.44 for per-protocol analysis; risk ratio = 1.25; 95% CI: 1.06 - 1.47 for intention-to-treat analysis). Conclusions: H. pylori infections decrease the serum levels of several types of vitamins, eradication of H. pylori could rescue its adverse effects, and antioxidant vitamin supplementation may improve the H. pylori eradication rate.